2016
DOI: 10.3892/ijo.2016.3583
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous expression of zinc-finger E-box-binding homeobox 1 plays a pivotal role in metastasis via regulation of miR-200c in epithelial-mesenchymal transition

Abstract: Although epithelial-mesenchymal transition (EMT) has been implicated as the pivotal event in metastasis, there is insufficient evidence related to EMT in clinical settings. Intratumor heterogeneity may lead to underestimation of gene expression representing EMT. In the present study, we investigated the expression of EMT-associated genes and microRNAs in primary colorectal cancer while considering intratumor heterogeneity. One-hundred and thirty-three multiple spatially separated samples were obtained from 8 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…Several previous studies have suggested that impaired miR-200 expression may lead to EMT initiation and eventually to cancer dissemination. Decreased expression of miR-200 has previously been reported at the invasive front of metastatic CRC (24,25,(31)(32)(33) (24). They concluded that miR-200c probably plays a pivotal role in CRC metastases.…”
Section: Discussionmentioning
confidence: 84%
“…Several previous studies have suggested that impaired miR-200 expression may lead to EMT initiation and eventually to cancer dissemination. Decreased expression of miR-200 has previously been reported at the invasive front of metastatic CRC (24,25,(31)(32)(33) (24). They concluded that miR-200c probably plays a pivotal role in CRC metastases.…”
Section: Discussionmentioning
confidence: 84%
“…Hur et al . observed decreased miR-200c ISH signal at the invasive front in late stage CRC [26], while this was not observed by another research group [27]. Paterson et al .…”
Section: Discussionmentioning
confidence: 93%
“…miR-200b was found to be down-regulated in tumour budding cells at the invasive front in 71% of cases [33] and is believed to have a tumour-promoting role in CRC by targeting RND3 and CDKN1B [35]. In addition to miR-200b , several published data also described decreased expression of miR-200c at the invasive front of the tumour in metastatic CRC cases [36,37,38]. Additionally, miR-200a/b/c were also found to be down-regulated at the invasive front of CRC cases with degraded basement membrane [39] but there is limited data in the literature about the expression of miR-141 and miR-429 at the invasive front.…”
Section: Discussionmentioning
confidence: 99%